Commodification of Intimacy within the Post-Soviet Space: A Case of Compensated Dating in Russia, Ukraine, and Belarus - Алёна Евгеньевна Сутормина; Christopher S. Swader; Екатерина Александровна Бунич; Ольга Владимировна Стрелкова (Journal of Economic Sociology, 2011)
Detailed description in the text